Shearing simulation of non-standard cable geometries for time-domain reflectometry-based slope monitoring applications - Martinez, Philip A. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Slope monitoring is the method of measuring different parameters that may lead to landslide. Current implementations include the use of inclinometers and other sensors that are buried underground. The use of Time-domain Reflectometry (TDR) has also been explored for use in slope monitoring, typically by detecting reflections from discontinuities due to shearing along coaxial cables buried in the ground. However, it is hampered by its inability to detect shear orientation as a consequence of the coaxial cross-sectional geometry of the cable. In order to have some mechanism to detect shear orientation, a cable model was created with a cylindrical inner conductor and rectangular tube outer conductor. The cable model was made to undergo shear simulations with edge and corner shear orientation. Other parameters that were varied in the simulations are the shear displacement and shear bandwidth. TDR was performed on the cable using custom input signals. The simulation results show that the reflected signal from the varies with shear orientation. The magnitude of reflection spikes obtained from the edge shear differs from that of the corner shear by 15.86% - 46.15%. The reflection coefficient also differs by 0.203% - 1.515%. The cable model was also compared with a cylindrical coaxial cable, where the magnitude of the reflection spikes from the cable model differs from the coaxial cable by 128.47% - 173.65%. The established trends in the simulation were verified using theoretical values of line impedances. The study confirms that a cable may register different reflections with respect to shear orientation, opening up possibilities to explore on cable geometry to develop cable structures customized for TDR-based slope monitoring.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Slopes (Soil mechanics) -- Stability; Slope stability monitoring; Time Domain Reflectometry (TDR).